Multiscale characterization of the human claustrum from histology to MRI - Navona Calarco; Skerdi Progri; Sriranga Kashyap; Shuting Xie; Claude Lepage; Donna Gift Cabalo; Boris C. Bernhardt; Alan C. Evans; Kâmil Uludağ (Proceedings of the National Academy of Sciences, 2026)
The claustrum is a thin, bilateral structure embedded deep within the human brain. Its widespread cortical connectivity has motivated perhaps the broadest range of functional hypotheses of any subcortical structure. Yet its complex, sheet-like morphology has hindered investigation in living humans, leaving a small in vivo MRI literature marked by large and often implausible discrepancies. Here, we construct a three-dimensional histological “gold standard” model of the human claustrum and systematically evaluate three ultra-high field 7-Tesla MRI datasets against this reference and its downsampled derivatives. We show that apparent discrepancies in MRI-based claustrum morphology arise primarily from resolution-dependent effects rather than contrast limitations, which transform the claustrum’s intricate sheet into an artifactually thickened ribbon. Despite this, submillimeter MRI reliably captures a dorsal “core” containing most claustral volume and cell density and encompassing major corticoclaustral connectivity, and at the highest acquired resolution (0.5 mm isotropic), the ventral claustrum’s extension into the temporal lobe is partially recovered, with uncertainty reflecting boundary imprecision rather than anatomical absence. Together, these findings overturn the view that the human claustrum is inaccessible to MRI and establish a foundation for future functional and clinical investigation in the living human brain.